Comparing the Effects of Dual‐Task Gait Testing in New and Established Ambulators With Lower Extremity Amputations. Issue 10 (5th April 2018) - Frengopoulos, Courtney; Payne, Michael W.C.; Holmes, Jeffrey D.; Viana, Ricardo; Hunter, Susan W.
Abstract: Background: Gait is a complex process that involves coordinating motor and sensory systems through higher‐order cognitive processes. Walking with a prosthesis after lower extremity amputation challenges these processes. However, the factors that influence the cognitive‐motor interaction in gait among lower extremity amputees has not been evaluated. To assess the interaction of cognition and mobility, individuals must be evaluated using the dual‐task paradigm. Objective: To investigate the effect of etiology and time with prosthesis on dual‐task performance in those with lower extremity amputations. Design: Cross‐sectional study. Setting: Outpatient and inpatient amputee clinics at an academic rehabilitation hospital. Participants: Sixty‐four individuals (aged 58.20±12.27 years; 74.5% male) were stratified into 3 groups; 1 group of new prosthetic ambulators with transtibial amputations (NewPA) and 2 groups of established ambulators: transtibial amputations of vascular etiology (TTA‐vas), transtibial amputations of nonvascular etiology (TTA‐nonvas). Interventions: Not applicable. Main Outcome Measures: Time to complete the L Test measured functional mobility under single and dual‐task conditions. A serial arithmetic task (subtraction by 3s) was paired with the L Test to create the dual‐task test condition. Single‐task performance on the cognitive arithmetic task was also recorded. Dual‐task costs (DTCs) were calculated for performance on the cognitive and gait tasks. Analysis of variance determined differences between groups. A performance‐resource operating characteristic (POC) graph was used to graphically display DTCs. Results: Gait performance was worse under dual‐task conditions for all groups. Gait was significantly slower under dual‐task conditions for the TTA‐vas ( P < .001), TTA‐nonvas ( P < .001), and NewPA groups ( P < .001). However, there was no between‐group difference for gait DTC. The 3 groups tested did not differ in the amount of cognitive DTC (DTCcog). Dual‐task conditions also had a negative impact on cognitive task performance for the TTA‐nonvas ( P = .02) and NewPA groups ( P  < .001). The TTA‐vas group had a slight improvement during dual‐task conditions and has a positive DTCcog as a result ( P  = .04). However, no between‐group differences were seen for DTCcog. The POC graph demonstrated that many individuals had a decrease in performance on both tasks; however, the gait task was prioritized for the majority (56.2%) of participants. Conclusions: Cognitive distractions while walking pose challenges to individuals regardless of etiology, level of amputation, or time with the prosthesis. These findings highlight that individuals are at risk for adverse events when performing multiple tasks while walking. Level of Evidence: II